Rhetorical reading in the Holy Quran text (Surah Al-Kahf as an example) (Journal of the College of Basic Education, 2022)
The Holy Qur’anic text represents the summit of the hump of the language of adversity, which God Almighty honored by making it the language of the last of His prophets and the best of His creation, Muhammad , when He said, “And We did not send any Messenger except in the language of his people.” He also made it the language of His Noble Book, which preserved it from deviation and slippage, and who made it the guardian of this. The noble language is from the arrows of the enemies and their poisons, and Surat al-Kahf, the focus of our research, is part of this noble text. It has dealt with the study of its rhetoric for the three levels, the first of which is the synthetic level, which includes the news, its multiplication, its meanings, the introduction, the delay, the separation, the connection, the request from the interrogative, the order, the prohibition, and the call, and the second of these levels is the semantic level, which represents the metaphor And its types, analogy, metaphor, metaphor, then the phonetic level of comma, repetition, counterpoint, and interview